ENZYME CONDUCTOMETRIC BIOSENSOR FOR FRUCTOSE DETERMINATION - O. Y. Dudchenko; V. N. Pyeshkova; O. O. Soldatkin; O. P. Soldatkin; S. V. Dzyadevych (Biotechnologia Acta, 2013)
The conductometric biosensor for fructose determination based on fructose dehydrogenase and potassium ferricyanide mediator as electron acceptor has been developed. The enzyme was immobilized on a surface of the conductometric transducer together with bovine serum albumin using crosslinking with glutaraldehyde. Working conditions of the discribed fructose biosensor were optimized. The results concerning influence of the buffer solution concentration and potassium ferricyanide concentration on the biosensor performance are given. The fructose biosensor is characterized by high signal reproducibility and selectivity to fructose. The developed conductometric biosensor can be successfully used for fructose monitoring in the procedures of food and clinical diagnostic.